ROBUSTA COFFEE BEANS INCREASE LEVELS OF TNF-α AS A RESPONSE TO Streptococcus mutans - Pujiana Endah Lestari; I Dewa Ayu Susilawati; I Dewa Ayu Ratna Dewanti; Roedy Budirahardjo (UPT Penerbitan Universitas Jember)
Coffee plant is commodity exports that wasencouraging because it has relatively high economicvalue in the world market. Coffee plantations aremanaged by people, and this day its grow continuallyin several provinces in Indonesia so expansion isincreasing continuously. Coffee production inIndonesia ranks the fourth largest in the world afterColombia, Brazil and Vietnam (Zainuddin andMurtisari, 1995; Simanihuruk and Sirait, 2010). Inaddition, the coffee plant is one of the leadingcommodities developed in Jember. Chemical contentof coffee such as flavonoids, xanthine, antioxidants,alkaloids, polyphenols can serve as a bitter taste,antibacterial, platelet aggregation. Thebioavailability of polyphenols coffee has also beenstudied (Scalbert et al., 2000; Coralie et al., 2006;Naziq, 2012).Namboodiripad and Srividya (2009) prove theexistence of the inhibition zone coffee against S.mutans. These bacteria are structurally andantigenetically express a surface protein that arecalled antigen I / II, B, Sr and PAC that have amolecular weight of 185 kDa. These antigens by theresearchers were assigned that play a role in thepathogenesis of dental caries, and its are effective asa vaccine in the prevention of dental caries. I/IIantigens of S. mutans have properties of adhesive,that the bacteria are used attachment to hostcomponents during colonize and infection, so itsbecome the focus of a number of researchers. Thesesurface-antigen proteins have an effect in theattachment of S. mutans with acquired pellicles ontooth surfaces (Yuliati, 2005). The immune responsesof dental caries were associated with cytokine suchas IL-1 β, α, IL-1 and TNF-α that were expressedodontoblast layer. It is said that bacteria excretion aextracellular virulence-immunomodulatory protein(VIP, which has a mitogenic effect on lymphocytes,suppress the immune response of the host andinduces production of IL-10, which is animmunosuppressor cytokines. So, VIP is animportant virulence factor produced microorganismsand closely associated with the pathogenicity ofbacteria (Gomes et al., 2006).Thereby, it is said that coffee could be expectedto inhibit dental caries by means of modulate theimmune response. The paradigm change stated thatthe tissue replacement turns into tissueregeneration that was cause approach of medicalmateria that geared to a biologically tissueimprovement. Biocompatible materials indicate thatit can be accepted by the body (Harty and Ogston(1995), and the coffee was clearly meets theserequirements.The current utilization of the coffee plant in themodulates an immune response against S. mutansthat is cause a dental caries that have not beenstudied, so arises problem how theimmunomodulatory potential of robusta coffeebeans against dental caries ?The general objective of this research is to analyzethe immunomodulatory potential of robusta coffeebeans against dental caries, whereas the aim inparticular is analyze the influence of robusta coffeebeans against TNF-α levels in response to S. mutans.